Chemical and Biological Hazards of Plastic Utensils Used for Cooking and Other Uses: A Review Article - Yunus, Tadamoun Sabah (Universitas Muhammadiyah Sidoarjo, 2025)
Packaging accounted for over 40% of the 380 million metric tons of plastic produced worldwide in 2015. A range of polymers, additives, and other substances, like coatings and adhesives, are used to make plastic packaging. Packaging may include unintentionally added components like contaminants, oligomers, or degradation products, as well as residues from production processes like solvents. A comprehensive understanding of all the compounds involved is necessary to characterize the risks associated with chemicals that may be released during package manufacturing, use, disposal, and/or recycling. The Chemicals Associated with Plastic Packaging database comprises the chemicals utilized in manufacture and/or found in final packaging items. Highlights: Plastic packaging made up over 40% of global plastic production in 2015. It contains both intentionally and unintentionally added chemicals. Risk assessment requires full knowledge of all associated compounds. Keywords: Chemical, Biological Hazards, Plastic Utensils, Cooking